Visitor motivation and destinations with archaeological significance in the Philippines - Medrana, Jack G.L.; Gonzalo, Richard Philip A. (2016)
Access online through this link: https://journals.upd.edu.ph/index.php/asp/article/view/5495/4929
Keywords: Intramuros (Manila); Historic sites; Heritage tourism; Tourist attitudes